Ovarian Teratoma-Related Paraneoplastic Neurological Syndromes - Lin, Jingfang; Wang, Minjin; Wang, Jierui; Li, Jinmei (Frontiers in Oncology, 2022)
Paraneoplastic neurological syndromes (PNSs) are a group of neurological disorders triggered by an underlying remote tumor. Ovarian teratoma (OT) is the most common histologic type of germ cell tumor in females. The most common PNSs associated with OT is anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. However, with the increasing number of new antibodies reported over the last decade, the clinical spectrum of OT-related PNSs is also expanding. Our knowledge of OT-related PNSs is still far from complete. Here, we provide a comprehensive review of the most recent findings in the field of OT-related PNSs, with a particular focus on their clinical and pathological characteristics. Overall, the description of neuronal antibodies in PNSs associated with OT strongly suggests that antibodies may be responsible for the clinical symptoms in some cases. OT-related PNSs are associated with various clinical manifestations, including anti-NMDAR encephalitis, limbic encephalitis, encephalomyelitis, progressive cerebellar syndrome and opsoclonus-myoclonus syndrome. The pathological characteristics of the OT suggest that the mechanism of PNSs is probably due to heteromorphic neurons in the tumor tissue, the ectopic expression of the antigens in neural tissue within the teratomas and patients’ unusual immune response. Despite the severity of the neurological syndromes, most patients with OT-related PNSs showed good neurologic response to early tumor resection combined with immunotherapy. To further advance the management of OT-related PNSs, additional studies are needed to explore this complex topic.